Aksum and the Bible: Old Assumptions and New Perspectives - Piovanelli, Pierluigi (Aethiopica, 2018)
The Aksumite Bible, as a cultural product of Late Antiquity, is still relatively obscure. Thus, in spite of the most recent advances in the field of Ethiopian studies—notably, the new radiocarbon dating of Gärima I and Gärima III Gospels—old scholarly opinions, such as the active role played by the famous fifthcentury Syrian Miaphysite refugees in Aksumite Ethiopia, are not only still uncritically repeated, but also used to build up even more extravagant theories. The time has come to reassess some basic issues about the Egyptian and Palestinian origins of the first missionaries and the nature of the Greek texts they brought with them, as well as the Ethiopian identities of the first translators and the chronological framework for their work.